Spatial and temporal variability of BTEX in Paris megacity: Two-wheelers as a major driver. (January 2019) - Salameh, T.; Sauvage, S.; Locoge, N.; Gauduin, J.; Perrussel, O.; Borbon, A.
Abstract: Besides their impacts on health, BTEX play an important role in the formation of secondary organic aerosols and ozone for which limit values are regularly exceeded in Paris megacity and Ile de France region. An enrichment by a factor of 3 in the C7C9 aromatic fraction in the Paris atmosphere compared to other northern mid-latitude cities was shown in 2013. Here, we combined different approaches to investigate the role of transport-related sources in such enrichment (gasoline composition and vehicle fleet composition): a statistical analysis of a large BTEX dataset including multi-year and multi-site measurements (traffic, background, tunnel) and a coupled experimental and modelling analysis of liquid and headspace composition of representative fuels distributed in Ile de France region (SP95, SP95 E10, and SP98). For the latter the experimental set-up was designed to analyze the composition of 87 VOCs from C2 to C17 in both liquid and headspace phases. The model is able to predict the headspace composition at ± 15% and with an R 2 > 0.9. First a strong positive spatial gradient in BTEX composition at traffic stations is observed, with higher TEX-to-benzene ratio in Paris center compared to the suburbs and outskirts up to a factor of 2. This gradient reflects differences in fleet composition especially gasoline powered vehicles in Paris with a larger proportion of two-wheelers (15% in 2012). This gradient is also consistent with the inter-annual increase of TEX-to-benzene ratios along with the doubling of two-wheelers use and the decrease in the number of passenger cars. The gasoline evaporation model cannot solely explain the observed spatial variability. Finally, we investigated the potential contribution of two-wheelers to the aromatic enrichment in IdF region by introducing an additional unburned gasoline term to the model. The results support the suggestion that two-wheelers are a potential contributor to this enrichment. Considering the high use of two-wheelers in other European cities such as London or Barcelona if Europe is to decrease transport-related air pollution and inner city traffic, policy makers should consider finding alternatives to the conventionally-powered two-wheelers and supporting electric two-wheelers for example. Highlights: An extensive dataset of ambient BTEX is analyzed since 2003 for Greater Paris. High spatial variability of BTEX at traffic sites compared to urban background sites. Gasoline composition of over 80 VOCs is determined in both liquid and headspace phases. Gasoline headspace composition is well simulated at ± 15%. Two-wheelers exhaust and gasoline emissions explain higher aromatics at traffic sites rather than gasoline evaporation.